Agricultural mechanization patterns in Nigeria: Insights from farm household typology and agricultural household model simulation - Takeshima, Hiroyuki; Nin-Pratt, Alejandro; Diao, Xinshen (International Food Policy Research Institute, 2013)
Anecdotal evidence indicates labor costs for farming in Nigeria are rising while levels of mechanization remain low. Information is scarce regarding the types of farm households that use mechanization in Nigeria and the potential demand for mechanization services among farmers. We apply cluster analysis to data from the Living Standards Measurement Study—Integrated Surveys on Agriculture project in Nigeria to identify associations between mechanization and farm household types. We then simulate an agricultural household model to assess the potential demand for mechanization services in southern Nigeria.